Dependency on chloride concentration and ‘in-sphere’ oxidation of H2O for the effective TiO2-photocatalysed electron transfer from H2O to [PdCln(H2O)4−n]2−n (n = 0–4) in the absence of an added sacrificial reducing agent - Kriek, Roelof Jacobus; Mahlamvana, Foster (Elsevier, 2012)
The photocatalytic reduction trends of palladium chloride aqua complexes, [PdCln(H2O)4−n]2−n (n = 0–4), have been investigated employing titanium dioxide (TiO2) as photocatalyst in the absence of an added sacrificial reducing agent (SRA). Solutions were prepared at those Cl−-concentrations that coincide with the maximum of each species and the photocatalytic reduction behaviour of Pd(II) at these chloride-concentrations is related to the complex present in greater abundance. The photocatalytic reduction rate trend is observed to have the following decreasing order: PdCl2(H2O)2 > [PdCl(H2O)3]+ > [Pd(H2O)4]2+ > [PdCl3(H2O)]− > [PdCl4]2−, with [PdCl4]2− showing resistance to photocatalytic reduction in the absence of an added SRA. It is postulated that oxidation of the coordinated water molecules impacts on the rate of reduction. For those complexes for which the ratio H2O:Cl− is greater than 50%, the oxidation of coordinated ‘in-sphere’ water molecules is working against an expected increase in the rate of reduction as predicted by the complexes’ standard reduction potentials. Interplay between thermodynamics and adsorption/interaction of the palladium species on the catalyst surface is clearly at work in this system.
Keywords: Chloride; Palladium; Photocatalytic reduction; Sacrificial reducing agent (SRA); Speciation